The Characteristic and Free Radical Scavenging Activity of Zinc Oxide Nanoparticles (ZnO-NPs) Synthesized using Noni (Morinda citrifolia L.) Fruits and Leaves Extract - Selvina Koesyamin; Tagor Marsillam Siregar; Antonius Herry Cahyana (Jurnal Kimia Sains dan Aplikasi, 2026)
Zinc oxide nanoparticles (ZnO-NPs) have gained considerable attention due to their unique properties, including high chemical stability, excellent sensing ability, and antibacterial activity. Biological synthesis of ZnO-NPs is a promising approach because of its sustainability and the availability of diverse natural reducing agents. Noni (Morinda citrifolia L.), traditionally used as a medicinal plant for over 2,000 years in Polynesia, contains phenolics and flavonoids that act as natural reducing agents. This study aimed to evaluate the effects of different plant parts (fruits and leaves) and solvent polarities (deionized water, ethyl acetate, and hexane) on the reducing ability of the extracts, as measured by ZnO-NP yield and free radical scavenging activity. The characteristics of ZnO-NPs after calcination were also evaluated. Solvent polarity significantly influenced reducing power and antioxidant activity, while no notable differences were observed between fruits and leaves. Fruit extracts prepared with ethyl acetate (semi-polar solvent) produced the highest ZnO-NPs yield (2.88 ± 0.11 mg), the strongest free radical scavenging activity (10.63 ± 0.65% inhibition/mg ZnO-NPs), and nanoparticles averaging 115.9 nm in size. Calcination at 100°C, conducted to eliminate residual moisture and stabilize the particles, resulted in an increase in the mean particle size from 115.9 nm to 313.6 nm. Morinda citrifolia-mediated ZnO-NPs could be utilized as effective bioactive additives in the development of active food packaging systems to prevent oxidative degradation.